The Romani experience in a world of domination of non-Romani normality - Reichel, Tomáš (Romano džaniben, 2023)
The text is based on interviews with two university-educated Roma, Zdeněk and Věrka. It presents their everyday experiences with the surrounding, mostly non-Romani, world. In order to emphasise the narrators’ agency, impressions and interpretations of these experiences, if thematized, are also presented. The author grounds his discussion of this material in the book Black Skin, White Masks, in which Frantz Fanon focuses on the inequality of group identities on the example of the lived experiences of colonised people. He identifies the power behaviours of the non-Roma as rooted in the normality of racial discourse and co-constructed by the perception of Romani identity as an overarching category. In his view this further enables the non-Roma to overlook the individuality of the Roma and to base the racist narratives and related practices on a normalised notion of a priori homogenised Romani difference. At the same time, the author emphasises the diversity of experiences of racism and the ability to recognise and respond to racism as situational and temporal.